Hypothermic oxygenated perfusion with defatting cocktail further improves steatotic liver grafts in a transplantation rat model. Issue 9 (9th June 2021) - Lin, Fan; Zhen, Fu; Yan, Xiong; Shaojun, Ye; Guizhu, Peng; Yanfeng, Wang; Qifa, Ye
Abstract: In this study, we evaluated the restoring and defatting effect of hypothermic oxygenated perfusion (HOPE) on severe steatotic liver grafts with a defatting cocktail (DF) in a rat model. Severe (≥60%) hepatic macrosteatosis was induced by a high‐fat diet (HFD) for 6 weeks, after which the rats were randomly divided into four following groups: Control group, with lean livers being preserved in static cold storage (SCS) at 0°C‐4°C for 45 minutes; SCS group, with a steatotic liver graft (SLG) being preserved in SCS at 0°C‐4°C for 4 hours; HOPE group, where SLG was perfused with 3‐hours HOPE followed by 1‐hours SCS; and HOPE + DF group, HOPE with the addition of DF. Graft function after orthotopic liver transplantation was assessed in terms of mitochondrial function (adenosine triphosphate [ATP], Glycogen), endoplasmic reticulum stress (PPY, GRP78, CHOP, and ATF‐6), cell apoptosis (Tunel assay, Caspase‐3), inflammatory level (HMGB1, TLR4, IL‐1β, IL‐6. TNF‐α, Factor V), and posttransplantation survival. HOPE protected steatotic liver grafts from microcirculation disturbance and endoplasmic reticulum stress and then promoted ATP and glycogen synthesis that improved mitochondrial function. Meanwhile, under conditions of ischemia‐reperfusion injury, it prevented nuclear injury and endothelial damage by suppressing the release of an inflammatory mediator. The high efficacy of HOPE was enhanced after the addition of the DF. DF agents cannot promote the lipid decomposition of the steatotic liver graft at 0°C‐4°C, but they can further improve steatotic liver and postoperative survival compared to the HOPE. The defatted steatotic liver grafts can be safely used in rat orthotopic liver transplantation. Abstract : Hypothermic oxygenated perfusion (HOPE) can reduce ischemia‐reperfusion injury by improving the microcirculation of steatotic liver graft, inhibiting endoplasmic reticulum stress, stabilizing mitochondrial function, promoting adenosine triphosphate (ATP) synthesis, and eliminating inflammatory factors. Despite the dissatisfactory lipid decomposition of the steatotic liver graft at low temperature, HOPE with defatting cocktail (DF) further improves steatotic liver grafts in transplantation rat model by improving the microcirculation and inhibiting the release of inflammatory factors compared to the HOPE group, thus optimizing the quality of steatotic liver graft.